Accuracy of the vivofit activity tracker. (17th August 2016) - Alsubheen, Sana'a A.; George, Amanda M.; Baker, Alicia; Rohr, Linda E.; Basset, Fabien A.
Abstract: The purpose of this study was to examine the accuracy of the vivofit activity tracker in assessing energy expenditure and step count. Thirteen participants wore the vivofit activity tracker for five days. Participants were required to independently perform 1 h of self-selected activity each day of the study. On day four, participants came to the lab to undergo BMR and a treadmill-walking task (TWT). On day five, participants completed 1 h of office-type activities. BMR values estimated by the vivofit were not significantly different from the values measured through indirect calorimetry (IC). The vivofit significantly underestimated EE for treadmill walking, but responded to the differences in the inclination. Vivofit underestimated step count for level walking but provided an accurate estimate for incline walking. There was a strong correlation between EE and the exercise intensity. The vivofit activity tracker is on par with similar devices and can be used to track physical activity.